APPLICATION OF THE CUSTOMER RELATIONSHIP MANAGEMENT (CRM) MODEL IN THE MARKETING AND SALES PROCESS OF AUSTRALIAN CATTLE AT PT. ELDIRA FAUNA ASAHAN - phoeja; Muhammad Amin; Afdhal Syafnur (Jurnal Teknik Informatika (Jutif), 2022)
Eldira Fauna Asahan who is engaged in Australian cattle farming in the cattle sales system does not yet have a web-based service where the marketing and sales processes are still done manually. The problems encountered, the authors implement the implementation of Customer Relationship Management (CRM) with the waterfall method. The waterfall method is a method that takes a systematic and sequential approach starting from the level of system requirements and then heading to the analysis, design, implementation and testing stages. It is called a waterfall because the stages that are passed must wait for the completion of the previous stage and run sequentially. Customer Relationship Management (CRM) is one of the strategies used by companies to better know and understand their customers, so that companies can provide the best service and foster better long-term relationships with their customers. The results according to admin needs include: managing order data, managing user data, managing sales report recaps, and conducting sales transactions and sales stock. Meanwhile, the results according to user needs include: placing an order, filling in the required data, making payment transactions. In conclusion, the implementation of Customer Relationship Management is carried out properly and appropriately, making the company's business performance more optimal. With the existence of a Web-Based Information System for Eldira Fauna, it aims to make it easier for customers to place orders for cattle so that the online process becomes more effective and efficient.